Boron, carbon and oxygen isotope data from micrite, brachiopods and bivalves from the Early Jurassic Toarcian Oceanic Anoxic Event in SW Europe - Simone A Kasemann; Tina Klein; Richard A Boyle; Clemens V Ullmann; Martin Aberhan; Anette Meixner; Luis Vitor Duarte; Timothy M Lenton; Veronica Piazza; Rachel A Wood (PANGAEA, 2025)
The Toarcian Oceanic Anoxic Event (T-OAE, (T-OAE, ~183 Ma; Early Jurassic) marks a global mass extinction coincident with dramatic changes in climate and ocean circulation, likely driven by large igneous province emplacement. Rapid CO2 release may have induced global warming, widespread ocean deoxygenation, and ocean acidification. To constrain the magnitude of ocean acidification, we present boron (δ11B), carbon (δ13C) and oxygen (δ18O) isotope data from three different carbonate components, lime mud (micrite), rhynchonellid brachiopods (including Soaresirhynchia bouchardi), and bivalves (oyster) Gryphaea. All samples were collected from shallow marine carbonate successions deposited in the NW Tethys: Barranco de la Cañada in Spain, deposited in the Iberian Basin, and Rabaçal/Fonte Coberta in Portugal, deposited in the Lusitanian Basin. Sampling ranged from the latest Pliensbachian Margaritatus Zone to the mid-Toarcian Bifrons Zone. Only data from micrite shows a temporary decrease in δ11B values during the T-OAE, recording an ocean acidification event, which we reproduce using a coupled biogeochemical model. The contrasting stability of δ11B values shown by bivalves and brachiopods suggests that the studied taxa may have been able to physiologically buffer changes in ocean pH, and are therefore poor targets for the interrogation of pH changes in Earth history.